2008
DOI: 10.1016/j.jembe.2008.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-induced oviposition in the brachyuran crab Cancer setosus along a latitudinal cline: Aquaria experiments and analysis of field-data

Abstract: Ovigerous females of Cancer setosus are present year-round throughout most of its wide range along the Peruvian/Chilean Pacific coast (2°S-46°S). However, their number of egg-masses produced per year remains speculative and as such has neither been considered in latitudinal comparisons of reproduction, nor for its fisheries management. In order to reveal the effect of temperature on egg-mass production and eggdevelopment, female C. setosus were held in through-flow aquaria under natural seasonal temperature co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 36 publications
2
38
0
1
Order By: Relevance
“…Quintana and Saelzer (1986) showed that zoeal development of C. setosus larvae of a population from Coliumo Bay (Concepción, central Chile) takes about 60 days under natural temperature conditions (13.5-14.6°C), while larvae from the Antofagasta region have a 1.5 times exceeded zoeal development at 16°C and show higher survival rates (Weiss et al 2009b), and larvae from Concepcion are capable to develop through all zoeal instars at lower temperatures. These Wndings indicate a better cold adaptation of larvae originating from a southern population (see also Fischer and Thatje 2008;Fischer et al 2009a) and from an evolutionary point of view could be considered ancestral to further abbreviated larval developments (Strathmann 1978), which is favourable for larvae from colder regions.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Quintana and Saelzer (1986) showed that zoeal development of C. setosus larvae of a population from Coliumo Bay (Concepción, central Chile) takes about 60 days under natural temperature conditions (13.5-14.6°C), while larvae from the Antofagasta region have a 1.5 times exceeded zoeal development at 16°C and show higher survival rates (Weiss et al 2009b), and larvae from Concepcion are capable to develop through all zoeal instars at lower temperatures. These Wndings indicate a better cold adaptation of larvae originating from a southern population (see also Fischer and Thatje 2008;Fischer et al 2009a) and from an evolutionary point of view could be considered ancestral to further abbreviated larval developments (Strathmann 1978), which is favourable for larvae from colder regions.…”
Section: Discussionmentioning
confidence: 79%
“…A unique physiological plasticity to respond to latitudinal and seasonal changes in temperature has been observed in reproductive traits of C. setosus. Among the most conspicuous characteristics is a synchronisation of a single egg batch release with seasonality at the species southernmost distribution boundary in central southern Chile (Puerto Montt, 41°44Ј S), contrasted by multiple annual ovipositions in northern Chile (Antofagasta, 23°45Ј S) (Fischer and Thatje 2008). In addition, a correlation of changes in egg energy contents and temperature was observed along latitude as well as in subsequent ovipositions in the same female (Fischer and Thatje 2008;Fischer et al 2009a).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…include a reduction in fecundity, increase in egg size and energy per offspring with increasing latitude (Clarke et al 1985;Shilling and Bosch 1994;Fischer and Thatje 2008). Such reproductive patterns seem evident at least in decapod crustaceans, prosobranch molluscs, and echinoderms (Thorson 1936(Thorson , 1950Clarke 1979;Clarke et al 1985;Pearse et al 1991;Thatje et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Such reproductive patterns seem evident at least in decapod crustaceans, prosobranch molluscs, and echinoderms (Thorson 1936(Thorson , 1950Clarke 1979;Clarke et al 1985;Pearse et al 1991;Thatje et al 2005). However, the mechanisms driving latitudinal patterns in reproduction are far from being fully understood although often related to adaptations to decreasing temperature and more pronounced seasonality towards higher latitudes (Clarke 2003;Pearse and Lockhart 2004;Thatje et al 2005;Fischer and Thatje 2008).…”
Section: Introductionmentioning
confidence: 99%